AKTUALISASI PENDIDIKAN MODERASI BERAGAMA DI MADRASAH - Muhamad Syaikhul Alim; Achmad Munib (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2021)
Abstract: This article describes Religious Moderation Education in Islam, especially about the portrait and development of religious moderation education in madrasas. The crucial issues to be answered regarding moderation education in Islam in Madrasahs are (1) What is meant by religious moderation? (2) What are the characteristics of religious moderation in Islam? (3) and how is the portrait and development of religious moderation education in madrasas? To answer this problem, library research is carried out by exploring various literatures in the form of books, articles, journals, scientific opinions related to Islamic moderation to then be analyzed descriptively . The findings of this study include: Islamic moderation is understood as a balance between strong beliefs and tolerance in which there are Islamic values that are built on the basis of a straight and moderate mindset and not excessive. Madrasas are seen as one of the Islamic educational institutions that have succeeded in bringing moderate Islam in their educational praxis, therefore they deserve to be examples of religious moderation education for other educational institutions. To strengthen madrasas, they can develop mainstreaming of Islamic moderation, among others through: formulating a vision and mission oriented towards Islamic moderation, developing a comprehensive curriculum that incorporates Islamic moderation values, optimizing habituation and madrasa culture as a strategy for internalizing Islamic moderation character values, and developing programs strengthening Islamic moderation. Keywords: Education, Religious Moderation, Madrasah. Abstrak: Artikel ini memaparkan Pendidikan Moderasi Beragama dalam Islam khususnya tentang potret dan pengembangan pendidikan moderasi beragama di madrasah. Adapun permasalahan krusial yang hendak dijawab terkait pendidikan moderasi dalam Islam di Madrasah yakni (1) Apa yang dimaksud moderasi beragama? (2) Bagaimanakah karakteristik moderasi beragama dalam Islam? (3) dan bagaimanakah potret dan pengembangan pendidikan moderasi beragama di madrasah?Untuk menjawab masalah tersebut ditempuh penelitian kepustakaan (library research) dengan melakukan eksplorasi berbagai literatur baik berupa buku- buku, artikel, jurnal, opini ilmiah terkait moderasi Islam untuk kemudian dianalisis secara deskriptif. Temuan dari kajian ini antara lain: Moderasi Islam dipahami sebagai keseimbangan antara keyakinan yang kokoh dengan toleransi yang di dalamnya terdapat nilai-nilai Islam yang dibangun atas dasar pola pikir yang lurus dan pertengahan serta tidak berlebihan. Madrasah dipandang sebagai salah satu institusi pendidikan Islam yang berhasilmembawakan Islam moderat dalam praksis pendidikannyakarenanya layak menjadi contoh pendidikan moderasi beragama bagi institusi pendidikan lainnya. Untuk memantapkan madrasah dapat mengembangkan pengarusutamaan moderasi islam antara lain melalui: perumusan visi dan misi berorientasi moderasi Islam, pengembangan kurikulum yang komprehensif yang menginsersi nilai-nilai moderasi Islam, Optimalisasi habituasi dan budaya madrasah sebagai strategi internalisasi nilai-nilai karakter moderasi Islam, dan mengembangkan program penguatan moderasi Islam. Kata Kunci : Pendidikan, Moderasi beragama, Madrasah.